IL-17–Mediated Immunity Controls Skin Infection and T Helper 1 Response during Experimental Microsporum canis Dermatophytosis - Burstein, Verónica Liliana (2018)
Despite worldwide prevalence of superficial mycoses, the immune response in dermatophytosis has scarcely been investigated. In this study, we developed a model of superficial skin infection in C57BL/6 mice with Microsporum canis, a highly prevalent human pathogen. This model mimics mild inflammatory human dermatophytosis, characterized by neutrophil recruitment and fungal invasion limited to the epidermis and exhibits the establishment of a specific T helper type 17 immune response during infection. By using IL-17RA- or IL-17A/F-deficient mice we showed that, in the absence of a functional IL-17 pathway, M. canis extensively colonizes the epidermis and promotes an exaggerated skin inflammation and a shift to an IFN-γ-mediated (T helper type 1) response. IL-17 signaling was not involved in neutrophil influx to skin or fungal invasion to deeper tissues. Finally, this study shows that skin langerin-expressing cells contribute to the antifungal T helper type 17 response in vivo. In conclusion, these data directly show a dual function of IL-17 cytokines in dermatophytosis by controlling superficial infection and down-modulating a T helper type 1 antifungal response.